Life and Health Insurance Under Ambiguity - Koltsidas, Anastasios (2009)
Life and health insurance are intangible services which promise to compensate in the future a person who begin to pay now. Insurance industry is tantalized from many problems like adverse selection and moral hazard. One of the major problems in insurance industry is the ambiguity. Ambiguity has implications to insurance companies and to individuals as they cannot predict precisely the loss probabilities. Purpose of this study is to investigate the main strategies Greek insurance representatives use to deal with consumers’ ambiguity. A new perspective of examining ambiguity is presented as no paper exist which investigated ambiguity by examining consumers and insurers the same time. Some illustrative results about consumers’ needs and methods to deal ambiguity are presented and some inabilities of Greek agents to overcome consumers’ ambiguity are presented.